Psychological Perspectives on Motivation through Gamification - Michael Sailer; Jan Hense; Heinz Mandl; Markus Klevers (Interaction Design and Architecture(s), 2014)
Gamification is an innovative approach to foster motivation. It refers to the use of game elements in non-game contexts. This article adopts a differentiated view on the topic of gamification and investigates, how and why different game elements can address different motivational mechanisms. At first, the concept of gamification and specific game elements characteristic of gamification are described. After that, different motivational perspectives were analyzed and motivational mechanisms in form of effect hypotheses were derived from these perspectives. To investigate the motivational pull of gamification, game elements are matched with motivational mechanisms. Our theoretical inquiry shows that gamification potentially addresses motivational mechanisms and thereby fosters motivation. These theoretical results can be used for the effective design of gamification environments and represent a basis for empirical research. Further research is required to confirm these theoretical findings.